Lady Rachel's dangerous Duke - Merrill, Christine (Harlequin historical, 2022)
Everyone has heard the whispers about the Duke of Scofield: that he killed his own father! But Lady Rachel knows he's innocent, because she was with him that fateful night. He's too honorable to clear his name by ruining her, but why has he cut her out of his life? Rachel must discover the whole truth if she's to have any chance of being with him...